2010
DOI: 10.1380/ejssnt.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Image of Escherichia Coli Exposed with Atmospheric-Pressure Plasma Jet

Abstract: The morphological change of Escherichia coli (E. coli) exposed to an atmospheric-pressure argon (Ar) plasma jet was observed by scanning electron microscopy (SEM). The Ar plasma jet was generated at a frequency of 9 kHz, applied voltage of 10 kV, and Ar gas flow rate of 10 L/min at atmospheric pressure. E. coli seeded on an agar plate in a Petri dish was disinfected by Ar plasma jet exposure for 2 seconds. SEM images showed that E. coli cells deformed and faded after the Ar plasma jet exposure. The morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…It has a gas temperature of approximately 30 °C and is a low-temperature plasma. 21) In our previous study, E. coli cells seeded on an agar medium in a Petri dish were inactivated by Ar plasma jet irradiation for 2 s. 22) In this study, we carried out an experiment to determine whether light from a plasma jet contributed to the inactivation of E. coli. In this experiment, a quartz plate with a transmittance ²95% for light with wavelengths of 200-1000 nm was inserted between the end of the quartz tube and the E. coli on the agar medium so that E. coli was irradiated with only light from the plasma jet.…”
Section: Introductionmentioning
confidence: 99%
“…It has a gas temperature of approximately 30 °C and is a low-temperature plasma. 21) In our previous study, E. coli cells seeded on an agar medium in a Petri dish were inactivated by Ar plasma jet irradiation for 2 s. 22) In this study, we carried out an experiment to determine whether light from a plasma jet contributed to the inactivation of E. coli. In this experiment, a quartz plate with a transmittance ²95% for light with wavelengths of 200-1000 nm was inserted between the end of the quartz tube and the E. coli on the agar medium so that E. coli was irradiated with only light from the plasma jet.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that Escherichia coli (E. coli) AB1157 on an agar medium was killed upon irradiation with an atmospheric-pressure Ar plasma jet in air for 2 s, on the basis of the proliferation of cultured E. coli and the scanning electron microscopy (SEM) observation results [12,13]. Because an SEM image of E. coli cells irradiated with a plasma jet showed that the cells were punctured but retained their original shape to a certain degree, we speculated that the structures of the cell wall and membrane were changed by Ar plasma jet irradiation.…”
Section: Introductionmentioning
confidence: 99%